Years of life lost to revolution and war in Iran - Mohammad Reza Farzanegan (Review of Development Economics, 2023)
How was life expectancy in Iran affected by the Islamic Revolution and subsequent war with Iraq? This study examines the joint effect of regime change and the war against Iraq on life expectancy in Iran between 1978 and 1988. If there had been no revolution and war in Iran, how would the life expectancy of Iranians have developed? To answer this question, we use a synthetic control model to construct a counterfactual Iran based on a weighted average of other comparable countries, which reproduces the situation of pre-revolution Iran but does not experience the revolution and war. We then compare the life expectancies of the counterfactual and actual Iran that underwent a regime change and war with Iraq. Our results indicate that an average Iranian's total life expectancy would have been approximately five years longer without the revolution and war. The revolution had a moderate long-term impact on total life expectancy at birth, with the most significant influence being attributed to the war itself, particularly on male life expectancy. Our main findings are robust to a series of tests, including placebo tests. We investigate possible reasons that may explain the impact on longevity.
Keywords: 330; conflict; human costs; Iran; Iraq; life expectancy; revolution; sanctions; synthetic control method; treatment effect; war